Measuring Wasting and Stunting Prevalence Among Children Under 5 Years of Age and Associated Risk Factors in Papua New Guinea: New Evidence From the Comprehensive Health and Epidemiological Surveillance System - Pham, Bang Nguyen; Silas, Vinson D.; Okely, Anthony D.; Pomat, William (Frontiers in Nutrition, 2021)
Background Papua New Guinea undergoes socio-economic changes and faces a health transition, where non-communicable diseases have been reportedly emerging. While under-nutrition such as wasting and stunting still remains high among CU5, 46%, overweight and obesity are reported on increase. Objective The study measures prevalence of wasting, stunting, underweight, and overweight among CU5 and explores potential household and maternal socioeconomic demographic associated risk factors in PNG. Method Data from 3132 CU5 derived from the Comprehensive Health and Epidemiological Surveillance System (CHESS) database, set up and operated by PNG Institute of Medical Research (PNGIMR) in five major provinces of PNG since 2010. Key child health and development indicators, including wasting, stunting, overweight and underweight are measured against the 2006 WHO Standard Growth Standards. Multivariate logistic regression analyses were conducted to identify socioeconomic determinants of these child health development outcomes. Result Prevalence of wasting was 13.8%; stunting at 46.5%, underweight at 18.2%, and overweight at 18% of all child participants. Logistic regression analysis showed that household food shortage in the past 12 months and household wealth are significant positive predictors of wasting and stunting among CU5. Children from households with food shortage experience are 1.43 times more likely to be wasted than those children from households without such experience (OR: 1.43 [95% CI: 0.93-2.21]). Children from poorer household wealth quintile are 1.2 times more likely to be stunted than those from richest quintile (OR: 1.2 [95% CI: 0.79-1.82]). Male children are more likely wasted than female counterparts (OR: 0.77 [0.53-1.11]). By contrast, factors associated with stunting are including residence in urban vs. rural areas (OR: 1.13 [0.8-1.6]), mother in union vs. single mother (OR: 0.86 [0.59-1.24]), mothers with vocational training vs. mothers with college/ university education (OR: 0.19 [0.02-1.6]). Conclusion An integrated approach is needed to comprehensively address the household socioeconomic factors at the household level, contributing to the improvement of child health and development in PNG.